2021
DOI: 10.1186/s11689-021-09387-w
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of telemedicine to support caregivers of young children with ASD and their Part C service providers: a comparison of intervention outcomes across three models of service delivery

Abstract: Background Families of young children with autism spectrum disorder (ASD) frequently experience barriers to accessing evidence-based early intervention services. Telemedicine presents an opportunity to increase access to these services, particularly for families in rural and under-resourced areas. The present article describes a brief behavioral intervention and support model for families of young children with concerns for ASD. In the context of the COVID-19 pandemic, this service model shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…We also observed very good agreement when the caller was the patient's father, or the patient himself, while agreement was less when other family members, friend, or caregiver mediated the call, although it was still good. This concurs with studies have similarly shown that during the current pandemic, parent-mediated teleassessment within the home environment was feasible for many medical conditions [ 49 , 50 ]. Hence, AD may be worthy in under-resourced and geographically isolated communities, where family members can contribute to remote patient evaluation [23] and improve the AD experience.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed very good agreement when the caller was the patient's father, or the patient himself, while agreement was less when other family members, friend, or caregiver mediated the call, although it was still good. This concurs with studies have similarly shown that during the current pandemic, parent-mediated teleassessment within the home environment was feasible for many medical conditions [ 49 , 50 ]. Hence, AD may be worthy in under-resourced and geographically isolated communities, where family members can contribute to remote patient evaluation [23] and improve the AD experience.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the available literature, approximately half of the parents and professionals in our study sample expressed concern about the child’s distraction induced by electronic devices and the home environment (e.g., sharing rooms with siblings, presence of young children or other family members, etc.) [ 39 , 56 , 57 , 58 ], which may reduce their willingness to participate in the diagnostic/therapeutic session. In light of these concerns, healthcare professionals should provide practical advice to families on the proper use of the devices and the optimal preparation of the home setting (limiting distractions at home, materials to be used during telematics sessions).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many studies have examined the efficacy of remote approaches for ASD diagnosis and intervention [ 37 , 38 , 39 , 40 , 41 , 50 , 51 ], parental satisfaction [ 52 , 53 , 54 ], perceptions of telemedicine, and its potential benefits and limitations after using the service remotely [ 39 , 55 , 56 , 57 , 58 , 59 ]. Although some studies to date have examined healthcare professionals’ and parents’ views after experiencing remote services for ASD [ 39 , 53 , 54 , 55 , 58 , 59 ], few studies have explored the opinions about telemedicine that providers and users have before its use [ 56 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the current pandemic, TD changed to be directly between the dental professional and patient, hence probably necessitating the mediation of a family member, guardian, or caregiver in some instances. A point is that while teleassessment within the home environment is feasible for many medical conditions (e.g., children with autism 31 , 32 ), TD could represent additional challenges. From the provider side, training for dentists is required to enhance their ability to provide precise information to patients/caregivers to perform delicate tasks, for example, compression to stop bleeding or undertaking oral hygiene measures.…”
Section: Discussionmentioning
confidence: 99%